2019
DOI: 10.1038/s41598-019-52556-0
|View full text |Cite
|
Sign up to set email alerts
|

Trpc1 as the Missing Link Between the Bmp and Ca2+ Signalling Pathways During Neural Specification in Amphibians

Abstract: In amphibians, the inhibition of bone morphogenetic protein (BMP) in the dorsal ectoderm has been proposed to be responsible for the first step of neural specification, called neural induction. We previously demonstrated that in Xenopus laevis embryos, the BMP signalling antagonist, noggin, triggers an influx of Ca2+ through voltage-dependent L-type Ca2+ channels (LTCCs), mainly via CaV1.2, and we showed that this influx constitutes a necessary and sufficient signal for triggering the expression of neural gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…In recent years, many important reports have demonstrated that Ca 2+ is essential for involuting/migrating mesodermal cells [ 71 , 72 ]. However, several reports suggest that Ca 2+ signaling interacts with other pathways and plays an inductive role in neural development in vertebrates; for details, readers may wish to consult the cited articles [ 71 , 73 , 74 , 75 , 76 ].…”
Section: Overview Of Major Signaling Pathways and Targets Involved In Organizer-induced Embryonic Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, many important reports have demonstrated that Ca 2+ is essential for involuting/migrating mesodermal cells [ 71 , 72 ]. However, several reports suggest that Ca 2+ signaling interacts with other pathways and plays an inductive role in neural development in vertebrates; for details, readers may wish to consult the cited articles [ 71 , 73 , 74 , 75 , 76 ].…”
Section: Overview Of Major Signaling Pathways and Targets Involved In Organizer-induced Embryonic Developmentmentioning
confidence: 99%
“…Similarly, Nog induces the interaction between Trpc1 (transient receptor potential canonical subfamily member 1, a calcium channel) and BMPRII (BMP receptor type II); this complex allows for the activation of several Ca 2+ channels and cations influx. Increased amounts of intracellular Ca 2+ activate Ca 2+ -mediated signaling pathways and activate neural genes’ expression [ 73 , 76 ]. However, Wnt antagonists are also important to maintain low Wnt activity in the anterior region, inhibit BMP transcription, and establish an endogenous Wnt/β-catenin signaling morphogen gradient along the neural axis, critical for neural development [ 11 ].…”
Section: The Organizer As An Organizing Center Of Vertebrate Embryonic Patterningmentioning
confidence: 99%
“…It has previously been reported from X. laevis embryos that localized, intracellular Ca 2þ transients triggered by planar signals can induce the expression of the Zic3 gene in the dorsal ectoderm during neural induction (Leclerc et al, 2003;Batut et al, 2005;Néant et al, 2019). We propose that an increase in pH i might be associated in some required/synergistic way with these Ca 2þ transients to induce the expression of important early primary genes known to regulate the subsequent expression of other essential neural genes (Nakata et al, 1997;Winata et al, 2013).…”
mentioning
confidence: 72%
“…It is not possible at this time to determine if bafilomycin A1 had a direct effect on the signal transduction pathway leading to the expression of Zic3, or if the effect was secondary; for example, resulting from a cessation of the morphogenic movements that contributed to gastrulation. However, it is becoming clear that neural induction is regulated via a complex interplay between cell-to-cell signalling, inductive interactions, morphogenetic movements, and localized gene expression (Keller et al, 1992;Nakata et al, 1997;Muñoz-Sanjuán et al, 2002;Leclerc et al, 2012;Stern, 2006;Néant et al, 2019). It will, therefore, require careful and extended experimentation to decipher exactly where and when the H þ fluxes occur (perhaps at various times and in different intracellular and/or embryonic locations) during the extended process of neural induction and subsequent neurogenesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation